Market Phoenixes and Banking Ducks Are Recoveries Faster in Market-Based Financial Systems? - Allard, Julien (IMF Working Papers; Working Paper, 2011)
Recoveries vary considerably across countries: our paper compares recoveries in bank-based and market-based economies and finds that market-based economies experience significantly and durably stronger rebounds than the bank-based ones (in particular the more bank-based economies of continental Europe). Further, stronger recoveries also tend to be associated with broader economic flexibility. Our findings suggest that dealing with bank sector vulnerabilities is paramount to support the recovery. In the medium term, structural policies to deepen financial markets are useful, but need to be complemented with structural measures to address rigidities more broadly in the real economy.